A biomechanical study regarding the effect of tissue harvesting from the thorax on its movement during inspiration. (12th March 2013) - Hatano, Asako; Nagasao, Tomohisa; Shimizu, Yusuke; Jin, Hongmei; Kaneko, Tsuyoshi; Cho, Yasunori; Jiang, Hua; Kishi, Kazuo
Abstract : Objective: In the practice of plastic surgery, ribs and cartilage are often harvested for use in auto-grafts. This study aimed to elucidate the effect of such harvesting on the inspiration movement of the thorax. Materials and Methods: Sixteen three-dimensional computer simulation models were produced by reference to the CT data of 16 patients. To simulate the harvesting of ribs and costal cartilages, parts were removed from these thorax models, thereby producing models with different types of defect. By performing finite element calculation after applying contracture forces on the external intercostal muscles and diaphragm, the movement patterns exhibited by the thoraces during inspiration were analyzed. The relationships between the defect types and the movement patterns were evaluated with reference to the dynamic behavior of the sternum and the increase in thoracic volume. Results: Although the removal of costal cartilage can cause asymmetric movement of the thorax, it did not affect the inspiration movement of the thorax. However, removal of two or more ribs not only caused asymmetric movement of the thorax, but also negatively affected that movement. Removal of two or three ribs impaired the expansion of the hemi-thorax on inspiration by 10% and 40%, respectively. Conclusion: The present study is the first to clarify the quantitative effect of tissue harvesting from the thorax on inspiration. The findings will be useful for surgeons when planning operations requiring harvesting of tissue from the thorax.